Navigating time and space: how Americans with disabilities use time and transportation. Issue 1 (1st January 2016) - Myers, Andrew; Ravesloot, Craig
Abstract: Inadequate transportation poses a major barrier to participation for people with disabilities. Most research on the relationship between transportation and participation has relied upon small-scale studies, which are not nationally representative. National time use surveys offer a means of investigating the impact of transportation on participation on a larger scale. We used 2008–2011 data from the American Time Use Survey to investigate how people with mobility impairments managed time throughout daily activities and how transportation use was associated with time use, and compared these results to people without impairments. The study sample included 32, 642 respondents between the ages of 18 and 65. Time use among people with and without impairment was generally similar, with the exception of major differences in watching television and working. Regression analyses suggest that lack of transportation impacts time use more than impairment. Further, even when accounting for the effect of transportation, people with impairments report higher levels of home-based activities like watching television, indicating that other factors, such as home accessibility, may also account for differences in time use.